The influence of social determinants of health on heat illness prevention and seeking/trusting information sources among Florida residents - Alejandro Mena; Andres F. Manrique; Ashley McLeod-Morin (Frontiers in Communication, 2026)
Heat-related illnesses (HRIs) are a growing public health concern, particularly in the context of global climate change. Vulnerable populations, such as agricultural and outdoor workers, face disproportionate risks of HRIs. This study investigates associations between social determinants of health (SDOH) profiles and prevention behaviors, trust in information sources, and frequency of information-seeking related to extreme heat among Florida residents. Using a Bayesian Profile Regression (BPR) approach, we identified four clusters based on six sociodemographic and contextual variables from an online survey administered to 500 Florida residents, including income, education, race/ethnicity, occupation, political orientation, and urban/rural status. Logistic regression models were then used to examine associations between these clusters and key HRI-related outcomes. Cluster 3, characterized by low income, low education, rural residency, agricultural work, and high proportions of Hispanic and Black people, showed elevated odds of low prevention and distrust in institutional information sources. Clusters 2 and 4 demonstrated more selective distrust of government-affiliated platforms. These findings underscore the need for targeted, culturally responsive health communication strategies tailored to the diverse SDOH profiles influencing heat-related vulnerability. Take-home message Social determinants of health profiles are associated with differences in prevention behaviors and trust in information sources during extreme heat. Populations characterized by lower income, lower education, and rural/agricultural backgrounds may experience greater heat-related vulnerability, highlighting the need for culturally responsive and targeted communication strategies.